The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ina.12807
|View full text |Cite
|
Sign up to set email alerts
|

Combining culturing and 16S rDNA sequencing to reveal seasonal and room variations of household airborne bacteria and correlative environmental factors in nanjing, southeast china

Abstract: Bioaerosols are ubiquitous in indoor and outdoor environment. 1 They are tiny airborne particles, usually ranging from 0.001 nm to 100 μm, containing pathogenic and non-pathogenic dead or alive microorganisms (bacteria, fungi, and virus). 2,3 Fine bioaerosols tend to suspend for a long time in the air, varying from several minutes and even hours depending on their size. [4][5][6] Exposure to bioaerosols potentially poses adverse health effects, including infectious and respiratory diseases, allergies, and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 78 publications
(239 reference statements)
3
16
1
Order By: Relevance
“…For bacterial diversity analysis, the universal primer (343F-5'-TACGGRAGGCAGCAG-3' and 798R-5'-AGGGTATCTAATCCT-3') was used to amplify the V3-V4 hypervariable regions of the bacterial 16S rDNA gene. 13 For fungal diversity analysis, the universal primer (ITS1F-5'-CTTGGTCATTTAGAGGAAGTAA-3' and ITS2-5'-GCTGCGTTCTTCATCGATGC-3') was used to amplify the ITS hypervariable regions. 38 The detailed information of the collected samples has been provided in Table 1.…”
Section: Next-generation Sequencing Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…For bacterial diversity analysis, the universal primer (343F-5'-TACGGRAGGCAGCAG-3' and 798R-5'-AGGGTATCTAATCCT-3') was used to amplify the V3-V4 hypervariable regions of the bacterial 16S rDNA gene. 13 For fungal diversity analysis, the universal primer (ITS1F-5'-CTTGGTCATTTAGAGGAAGTAA-3' and ITS2-5'-GCTGCGTTCTTCATCGATGC-3') was used to amplify the ITS hypervariable regions. 38 The detailed information of the collected samples has been provided in Table 1.…”
Section: Next-generation Sequencing Analysismentioning
confidence: 99%
“…29 Zhai et al 30 proposed that the 'inhalable coarse particles' with a diameter of 2.5 to 10 μm and the 'fine particles' smaller than 2.5 μm in diameter can enter the human inner body, 31 while most of the bioaerosols larger than 10 μm will deposit in the upper respiratory tract. 32 Ye et al 13 also revealed that particles <4.7 μm size range could penetrate the lower respiratory tract, such as the trachea, bronchus and alveolus. 13,33 Thus, the identification of factors that could affect the size distribution of bioaerosols in a built environment is important, as many studies have shown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with short-read next-generation sequencing (NGS), 16S rDNA gene amplicon-based metagenomic analysis of bacterial communities is possible and relatively straightforward (1). At present, 16S rDNA sequencing has been widely incorporated in the field of science, including food analysis (2)(3)(4), environmental surveys (5,6), and clinical tests (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%